Digital Due Diligence - Assessment of Digital Growth Potentials - Anja Konhäuser; Stefan Sambol; Toni Stark; Alexander Hahn (Marketing Review St.Gallen, 2023)
Digital markets are based on other mechanisms than classic markets. Due diligence analyses the present position and future potential of a business. This research aims to develop a conceptual framework of relevant dimensions that encompasses digital due diligence. Haniel's acquisition of the startup Emma is used to illustrate the practical application of this framework.
Keywords: 650